Productivity of prolific sheep : Economic analysis - I. Inounu; T.D. Soedjana (Indonesian Center for Animal Research and Development (ICARD), 1998)
The existence of major gene in the Indonesian sheep breeds has been revealed in three different genotypes which are further implied that different levels of feeding and management are necessary to realize the potential benefits for each genotype . The variability in the ewe production as a result of the differences in genotype and management levels were then evaluated by economic analysis . The result shows that improvement in management practices resulted in an increase of production ofindividual breeding ewe (BS). However, since these increases in performance required additional cost for higher input value, as it was indicated in the total production cost, attention must be given toward the decision as to which genotype to raise at what level of feeding management . This study has shown promising results to facilitate the decision makers in that direction, for example, ewes with FecJFFecJ` genotype gained the highest gross margin when they were treated with high level of feeding management. The next best alternative was followed by FecJ FFecJ F genotype. Furthermore, in the situation where low level of feeding management being practiced, ewes carrying the FecJF gene did not show their superiority since they gained lower gross margin compared with the non-carrier ewes. Key words : Prolific sheep, gross margin